Innovations and startups for tourism recovery - Perepelitsia, D. M. (ТДАТУ, 2020)
It should be noted that the tourism industry will manage to renew itself, with innovation and technology continuing to play a central role in these efforts. Supporting startups and companies is a key to contribution to the entire spectrum of economic sectors that benefit from tourism.
Keywords: people working in tourism; tourism; COVID-19